Brain tumours in south Brazil a retrospective study of 438 cases - Torres,Luiz Fernando Bleggi (1990)
All brain tumours diagnosed since 1967 in a University Hospital in the Southern region of Brazil were reviewed and clinical information concerning age, sex, symptoms and evolution were analysed. 88.1% of tumours were primary neoplasms and the rest secondary deposits. There was a male predominance and the second and fifth decades of life were the most affected. The main presenting symptoms were headache, vomiting, hemiparesis, loss of vision and epilepsy. The commonest tumour was of astrocytic origin (36.3%) amongst which the malignant ones, including glioblastoma multiforme, predominated. These tumours were frequent in the cerebral hemispheres (31.3%), particularly in the frontal lobes. The time of evolution from the beginning of the clinical manifestations until the first hospital admission was also studied. The authors discuss the clinical and pathological observations in relation to other large series analysed in the literature.